Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2340/16501977-2616
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial factors associated with poor health-related quality of life after minor to moderate transport-related injuries: Insights into the Victorian compensable population

Abstract: Transport-related injuries are a leading cause of disability and mortality. The literature indicates that while some of these injuries are severe and catastrophic, most are classified as minor and moderate. In practice, it is expected that patients with minor and moderate injuries will recover with no serious consequences. However, recent research shows that, while half of patients recover relatively quickly, the other half experience long-term physical and mental health disabilities. The current study found m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Associated with ageing, there is a gradual loss of cognitive abilities, explained by several factors, including changes in brain plasticity [ 2 ]. Traumatic events, even mild ones, can trigger or accelerate senile evolution due to the decrease in neurocognitive capacity; thus, cognitive changes can appear, such as distorted consciousness, confusion, altered attention, thought, perception, and memory [ 20 , 32 , 46 , 47 , 48 , 49 ]. A return to the previous mental state often occurs within a few days of the causal event.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Associated with ageing, there is a gradual loss of cognitive abilities, explained by several factors, including changes in brain plasticity [ 2 ]. Traumatic events, even mild ones, can trigger or accelerate senile evolution due to the decrease in neurocognitive capacity; thus, cognitive changes can appear, such as distorted consciousness, confusion, altered attention, thought, perception, and memory [ 20 , 32 , 46 , 47 , 48 , 49 ]. A return to the previous mental state often occurs within a few days of the causal event.…”
Section: Discussionmentioning
confidence: 99%
“…A return to the previous mental state often occurs within a few days of the causal event. Nevertheless, it can also initiate neuropsychological dysfunction, which can progress to pseudodementia or dementia and can unmask previously unknown mental health conditions, leading to a significant reduction in health and functional status, with loss of autonomy and independence, and, consequently, a decrease in quality of life after trauma [ 20 , 46 , 50 ]. Studies have also shown a relationship between physical impairment and adverse psychiatric outcomes in people with a prior history of mental illness [ 50 ], with an increased disability expected in these cases [ 32 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, Prang et al (2015) revealed a hierarchy of support following a transport-related accident such that injured patients relied the most on closer and more stable circles (e.g., family structure and spouses), followed by less stable circles (e.g., friends and neighbors); being married or in a relationship and support from family and friends were associated with better physical health. However, this prior work is limited and has primarily focused on hospitalized patients (Holeva et al, 2001; Kendrick et al, 2018; Nickerson et al, 2017; Perry et al, 1992), on trauma survivors months to years after the inciting event (Clapp & Beck, 2009; Kaniasty & Norris, 2008; Ozer et al, 2003), or on physical health or functional outcomes versus psychological outcomes (Prang et al, 2015; Samoborec et al, 2020). Taken together, the relationship between specific sources of perceived social support and psychological outcomes following injury remains relatively unexplored, particularly among those with acute but relatively mild to moderate noninterpersonal, accidental injury.…”
Section: Introductionmentioning
confidence: 99%